MKRN1 promotes colorectal cancer metastasis by activating the TGF-β signalling pathway through SNIP1 protein degradation - Yi Zhang; Qin-shan Li; Hong-lin Liu; Hong-ting Tang; Han-lin Yang; Dao-qiu Wu; Yu-ying Huang; Li-cheng Li; Li-hong Liu; Meng-xing Li (Journal of Experimental & Clinical Cancer Research)
Abstract Background The Makorin ring finger protein 1 (MKRN1) gene, also called RNF61, is located on the long arm of chromosome 7 and is a member of the RING finger protein family. The E3 ubiquitin ligase MKRN1 is closely linked to tumour development, but the exact mechanism needs to be elucidated. In this study, we aimed to investigate the specific mechanism and role of MKRN1 in colorectal cancer (CRC) development. Methods MKRN1 expression in CRC was analysed using the Cancer Cell Line Encyclopaedia and the Cancer Genome Atlas (TCGA) databases. Rectal tumour tissues were frozen to explore the MKRN1 expression in CRC and its clinical significance. The impact of MKRN1 on CRC cell proliferation and migration was observed using CCK8, colony formation, wound healing, and transwell assays. A combination of MKRN1 quantitative proteomics, ubiquitination modification omics analysis, and a string of in vitro and in vivo experiments revealed the potential mechanisms by which MKRN1 regulates CRC metastasis. Results MKRN1 expression was significantly elevated in CRC tissues compared to paracancerous tissues and was positively linked with prognosis (P < 0.01). MKRN1 downregulation inhibits CRC cell proliferation, migration, and invasion. Conversely, MKRN1 overexpression promotes the proliferation, migration, and invasion of CRC cells. Mechanistically, MKRN1 induces epithelial-mesenchymal transition (EMT) in CRC cells via ubiquitination and degradation of Smad nuclear-interacting protein 1 (SNIP1). Furthermore, SNIP1 inhibits transforming growth factor-β (TGF-β) signalling, and MKRN1 promotes TGF-β signalling by degrading SNIP1 to induce EMT in CRC cells. Finally, using conditional knockout mice, intestinal lesions and metastatic liver microlesions were greatly reduced in the intestinal knockout MKRN1 group compared to that in the control group. Conclusions High MKRN1 levels promote TGF-β signalling through ubiquitination and degradation of SNIP1, thereby facilitating CRC metastasis, and supporting MKRN1 as a CRC pro-cancer factor. The MKRN1/SNIP1/TGF-β axis may be a potential therapeutic target in CRC.